Xanthine oxidase inhibitory and DPPH radical scavenging activities of some primulaceae species - Norlida Mamat,; Jamia Azdina Jamal,; Ibrahim Jantan,; Khairana Husain, (Universiti Kebangsaan Malaysia, 2014)
Xanthine oxidase (XO) is an enzyme that catalyzes the metabolism of hypoxanthine and xanthine into uric acid. XO also serves as an important biological source of free radicals that contribute to oxidative damage involved in many pathological processes. Antioxidant effects of several Primulaceae species have been reported but their XO inhibitory activity has not been investigated. Thus, this study was conducted to determine the XO inhibitory and free radical scavenging activities of Primulaceae species and to correlate these activities with their total phenolic contents (TPC). A total of 129 extracts of different plant parts of twelve Primulaceae species were assayed for XO inhibition spectrophotometrically at 290 nm using allopurinol as a positive control. The antioxidant activity was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and TPC of the extracts were determined by the Folin-Ciocalteau method. The Pearson correlation analysis indicated that the TPC of the extracts showed moderate positive correlations with XO inhibition (r=0.31, p<0.05) and DPPH antioxidant activity (r=0.31, p<0.05) for all of the dichloromethane extracts. Amongst the extracts tested, the dichloromethane extract of the roots of Labisia pumila var. alata showed the strongest inhibitory effects for XO (IC50 4.8 μg/mL) and DPPH free radical capacity (IC50 1.7 μg/mL). The results suggested that Primulaceae species, particularly the dichloromethane extract of L. pumila var. alata roots, are the potential source of useful leads for the development of XO inhibitors.